Students’ Ability in Translating Noun Phrase - Jamaluddin Nasution; Balqis Wandira; Chitra Latiffani (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The research aims to find out how the students’ ability in translating noun phrase, at the third grade of Madrasah Aliyah Swasta (MAS) Amaliyah Sunggal, Medan. This research used qualitative research design; the subject of the research were 30 students of the second grade of Madrasah Aliyah Swasta (MAS) Amaliyah Sunggal, Medan. The instruments used in this research were test and interview. The researchers gave essay test for the students. The findings of the research found that 40% students were able to identify the translating noun phrase and 60% students were unable to do so. The students’ difficulties in translating noun phrase are found since the students’ lack of vocabulary understand and lack of translating in a sentence, but they can translate a word. It is suggested that the teacher should pay more attention to the students’ creating of better translation especially in the form of translating noun phrase.